Variational Monte Carlo study of light nuclei
An outstanding problem in Variational Monte Carlo (VMC) calculations with realistic interactions like Argonne V18 and Urbana IX three-body interactions is that p-shell nuclei turn out to be grossly under bound as compared to the Green’s Function Monte Carlo (GFMC) calculations. A similar situation exists in Diffusion Monte Carlo calculations with somewhat simplified interactions. In this thesis, we improve upon the VMC calculations by bringing about several variations in the established procedure of performing variational calculations. In the first variation, the effect of the errors as a function of the number of particles in the variational wave function are analyzed and then a correction through expanding the radial part in terms of a complete set are made and treat the expansion coefficients as variational parameters. Second variation consists in modifying the variational wave function structure. The state of the art variational wave function for s- and p-shell nuclei consists of two parts, where the first part is a Jastrow part operated upon by a symmetrized sum of two-body operatorial correlations and in the second part this outcome is then operated by a sum of unity, operatorial threebody and spin-orbit two-body correlations. A considerable improvement is obtained over the binding energies, wave functions and variance for the light nuclei 3H, 4He and 6Li by using these two variations. We obtain noticeable improvement in the quality of the wave function and lowering of the energies compared to earlier results. The new energies are –8.38 MeV, –28.07 MeV and –29.90 MeV for 3H, 4He, and 6Li respectively. All the computations have been taken away on a multiprocessor machine developed indigenously